Blockchain for industry 4.0 : emergence, challenges, and opportunities - S., Anoop V. (Boca Raton, FL : CRC Press, 2023)
"The text presents in depth coverage of theoretical concepts, and applications and advances in the field of blockchain technology. It will serve as an ideal reference text for graduate students and academic researchers in diverse engineering fields such as electrical, electronics and communication, computer, and information technology"--
OCLC-licensed vendor bibliographic record.
Keywords: Blockchains (Databases) -- Industrial applications; Industry 4.0.; COMPUTERS / Computer Engineering; TECHNOLOGY / Electronics / General